2002
DOI: 10.4049/jimmunol.169.10.5955
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Role of p38 Mitogen-Activated Protein Kinase in Mediating the Anti-inflammatory Effects of CpG Oligodeoxynucleotide in Murine Asthma

Abstract: DNA containing unmethylated CpG motifs is intrinsically immunostimulatory, inducing the production of a variety of cytokines and chemokines by immune cells. The strong Th1 response triggered by CpG oligodeoxynucleotide (ODN) inhibits the development of Th2-mediated allergic asthma in mice. This work documents that CpG ODN-induced IL-12 production plays a critical role in this process, because intrapulmonary CpG ODN inhibits allergic inflammation in wild-type but not IL-12−/− mice. CpG ODN rapidly localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…This hypothesis is supported by our observation that even though the persons with emphysema have abstained from smoking for months, their pulmonary p-ERK activity is significantly higher than that of active smokers without the disease. In addition, these data demonstrate that cigarette smoke activates MMP-1 in the absence of a complete inflammatory program, as shown by our epithelial culture system, providing further support for chronic obstructive pulmonary disease research efforts targeted at not only proteolytic enzymes, but also the internal signaling pathways of cells of the lung (47,48).…”
Section: Discussionsupporting
confidence: 73%
“…This hypothesis is supported by our observation that even though the persons with emphysema have abstained from smoking for months, their pulmonary p-ERK activity is significantly higher than that of active smokers without the disease. In addition, these data demonstrate that cigarette smoke activates MMP-1 in the absence of a complete inflammatory program, as shown by our epithelial culture system, providing further support for chronic obstructive pulmonary disease research efforts targeted at not only proteolytic enzymes, but also the internal signaling pathways of cells of the lung (47,48).…”
Section: Discussionsupporting
confidence: 73%
“…p38 MAPK has been reported to be involved in IL-12 production (21, 38). Recent reports have also revealed that SB202190, a p38 MAPK inhibitor, inhibits CpG oligodeoxynucleotide-induced IL-12 production in macrophages (39). However, the p38 MAPK inhibitors did not affect the p43-induced NF-B DNA-binding activity (data now shown), suggesting that p43 induced IL-12 production in macrophages via two independent pathways, the NF-B and PKC/p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 76%
“…Activation of TLR9 by CpG oligos triggers stress kinase (28,29) and NF-B (30) signaling pathways, leading to the activation of multiple transcription factors, which in turn up-regulate cytokine secretion and expression of cell surface markers. In the present study, treatment of J774 cells with RpG oligos and immunomers led to the activation of NF-B and phosphorylation of p38 in J774 cells, as occurred also with CpG oligos, suggesting that similar signaling pathways were involved in both cases (Fig.…”
Section: Discussionmentioning
confidence: 99%